Baseline BMI is associated with clinical symptom improvements in first-episode schizophrenia: a longitudinal study - Chen, Xiaofang; Fan, Yong; Ren, Wenchao; Sun, Maodi; Guan, Xiaoni; Xiu, Meihong; Li, Shuyun (Frontiers in Pharmacology, 2023)
Background: There is sufficient evidence of the high prevalence of obesity in schizophrenia (SZ) compared to the general population. Previous studies have reported that weight gain correlated with the response to antipsychotics in patients with SZ. Nonetheless, the relationship between body mass index (BMI) and therapeutic benefits remains unclear. This study was designed to investigate the association between baseline BMI and improvements in clinical symptoms after treatment with antipsychotics in first-episode and medication-naï ve SZ (FEMNS).Methods: A total of 241 FEMNS patients were enrolled and received risperidone over 12 weeks.The severity of symptoms was assessed by the Positive and Negative Syndrome Scale (PANSS) and BMI was measured at baseline and 12-week follow-up.Results: We found that risperidone treatment raised the body weight of FEMNS patients and baseline BMI was negatively correlated with weight gain after 12-week treatment. Linear regression analysis indicated that baseline BMI was an independent predictor of response to risperidone in the early stage of SZ.Conclusions: The current study suggests a close relationship between baseline BMI and improvement in negative symptoms in SZ.